Do we forget the public when we publish? A modest proposal so as not to forget what we think for - Seoane Pinilla, Julio (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
First, this article will discuss the way in which those of us who reflect in the public sphere have chosen to publish by submitting to the standards of academic excellence provided by the companies that measure scientific quality. Secondly, I will argue that this has led us to bet on the applause of our peers and to forget the spaces of intervention to which our reflection was originally intended to be directed. This being the situation, this article suggests including our work under another scale of excellence whose objective is the social and civic performance of thought under the conviction that democracy needs a reflection that is situated and not concerned with publication scales
Keywords: Evaluation Policy, epistemic decolonization, epistemicide, transgresion as research pattern.